2017
DOI: 10.1155/2017/8268701
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perception toward the Built Environment in Airport Access Mode Choice Using Hybrid Choice Modeling

Abstract: Built environment (BE), as an objective variable, plays a substantial role in urban residents’ behavior. However, the perception toward a BE, as a subjective variable, varies among people. To identify the role of perception toward BE, we used a stated preference (SP) survey conducted in January–February 2015 at the Imam Khomeini International Airport (IKIA), Tehran, Iran. The data was drawn from 641 individuals; 359 of them were residents of Tehran. For the estimation of the model, a hybrid discrete choice mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(84 reference statements)
1
3
0
Order By: Relevance
“…Most notably, constructs such as general attitudes and personality traits are considered useful for explaining rather than predicting behavior ( 5 ). These relationships and predictive powers were confirmed in more recent studies of travel behavior, with Yazdanpanah and Hosseinlou ( 6 ) considering the impacts of personality trait LVs, and Paulssen et al ( 7 ) the LVs of values (which are comparable to general attitudes and closer to personality traits than any other psychological constructs). Both found that these more abstract psychological LV constructs had no statistically significant effect on behavior, unless mediated by other, more choice-specific psychological constructs.…”
Section: Relevant Concepts and Their Utilizationsupporting
confidence: 55%
“…Most notably, constructs such as general attitudes and personality traits are considered useful for explaining rather than predicting behavior ( 5 ). These relationships and predictive powers were confirmed in more recent studies of travel behavior, with Yazdanpanah and Hosseinlou ( 6 ) considering the impacts of personality trait LVs, and Paulssen et al ( 7 ) the LVs of values (which are comparable to general attitudes and closer to personality traits than any other psychological constructs). Both found that these more abstract psychological LV constructs had no statistically significant effect on behavior, unless mediated by other, more choice-specific psychological constructs.…”
Section: Relevant Concepts and Their Utilizationsupporting
confidence: 55%
“…The typical Type 1 model is a model of access mode choice to a specific airport. This type of model has been developed for several airports in the US [1,2,4,24], Europe [5,9,10,23,43], and Asia [3,14,29,36,38,39,44,45]. Also Type 1-models when rail is the main mode exist [42], even though it is not at all as common.…”
Section: Stand-alone Models Of Connection Trips (Type 1 2 and 3)mentioning
confidence: 99%
“…Land use planning contributes to alleviating the influence of transportation on environment by determining the human activities' basic spatial settings. Therefore, various researches have focused on analyzing the connection of built environment and travel behavior at the time of the current study [34][35][36]. Based on New York Metropolitan Region dataset, Chen et al [13] assessed the impact of density on travel mode choice decisions for commuting trips under the condition of controlling for confounding factors.…”
Section: Influence Of Built Environment Features On Travel Behaviormentioning
confidence: 99%